A Cross-organizational Ecology for Virtual Communities of Practice in Higher Education - Mavri, Aekaterini; Ioannou, Andri; Loizides, Fernando (My University, 2019)
This work investigates Communities of Practice (CoPs) that support social learning in higher education. While most CoP research has taken place in single-stream contexts (e.g. in a university), this study reports on the ecology of a cross-organizational community (university and industry stakeholders) in the context of the formal curriculum. The work examines the role of technology configurations in supporting CoPs in Design and related studies. It also reports on the type and level of technology adoption, focusing on the learner perspective. This study’s CoP is made up of 21 third-year university students and ten external stakeholders (mentors, clients and industrial experts). The study concludes with a set of guidelines for the design and evaluation of similar CoP technology configurations. Key guidelines suggest a) supporting enhanced awareness of identity, space and time, b) enabling roles and permissions on-demand according to the requirements of the activities carried out in shared spaces and c) facilitating fluid interoperability between the domain-specific and mainstream/generic productivity tools used by the community. The outcomes of this work can assist instructors, researchers and practitioners in the design of similar technology configurations for CoPs in the formal curricula of their respective Design or relevant fields.
Keywords: Situated Learning; Communities of Practice; Design in Higher Education